ordnet.dk – et nyt sprogligt opslagsværk på internettet - Lorentzen, Henrik; Trap-Jensen, Lars (Nordiske Studier i Leksikografi, 2006)
ordnet.dk – a new lookup tool on the Internet. We give an account of the architecture and functionalities of a web-based application that gives joint access to three existing resources and seeks to combine them in a new way. The project includes digitisation of the historical 28-volume dictionary Ordbog over det danske Sprog (Dictionary of the Danish Language) as well as the integration with its five supplementary volumes. The modern Den Danske Ordbog (The Danish Dictionary) will continuously be supplied with new material and adapted to a concept for a digital dictionary which will among other things introduce new features such as onomasiological queries and larger integration with the Korpus 2000 component. The corpus module is supplied with additional material, and a revision of both the interface and functionalities of the module is foreseen as part of the project which runs until the end of 2009.